High power nano-Nb2O5 negative electrodes for lithium-ion batteries. (20th February 2016) - Lübke, Mechthild; Sumboja, Afriyanti; Johnson, Ian D.; Brett, Dan J.L.; Shearing, Paul R.; Liu, Zhaolin; Darr, Jawwad A.
Graphical abstract: Highlights: High surface area semi-crystalline Nb2 O5 can be directly synthesized via CHFS. The as-obtained Nb2 O5 displayed excellent electrochemical performance. At high current rates, the Nb2 O5 behaved like an oxide supercapacitor material. Pseudocapacitive reactions contributed to >63% of the total charge at 5 mV s −1 . Abstract: Nano-sized, semi-crystalline niobium pentoxide (Nb2 O5 ) was synthesized in a single step via a continuous hydrothermal process. The nanomaterial was characterized using a range of analytical techniques including powder X-ray diffraction and transmission electron microscopy. The "as-prepared" Nb2 O5 nanomaterial was investigated as negative electrode for a lithium-ion battery and was shown to be stable during electrochemical cycling (98.6 % capacity retention after 800 cycles) and showed promising high rate performance, with a specific capacity of 43 mAh g −1 at an applied current of 10, 000 mA g −1 (in the wide potential range of 0.05 to 3 V vs Li/Li + ). Scan rate tests were used to investigate the proportion of stored charge from diffusion-limited processes and that from surface effects, which showed that at higher currents, charge storage from the latter was dominant.